Condiciones turísticas para la práctica del turismo de aventura en la provincia de San Martín, departamento de San Martín. - Llontop López, Dora Cristina (2016)
The present research work is based on the Tourist Conditions of the Province of San Martin, Department of San Martin for the development of Adventure tourism, a study was carried out on natural resources, accessibility to resources, support of the Authorities and the willingness of the host community to provide tourist services to visitors._x000D_ As a result of this research, the Province of San Martin has a great tourist potential to develop different types of adventure sports, all of which are complemented by the support of the local authorities and the availability of the receiving community to be Involved in the development of adventure tourism in their communities, including the access roads to the Province of San Martin are totally asphalted and in good conditions, likewise, the access roads to the resources are roads affirmed, both are in Good state, there is a great diversity of companies that the tourist can choose to reach the Province of San Martin, from river, air and land transport companies, all have what is necessary to make the trip pleasant, the local authorities of The Province of San Martin (mayor and others), have the political will to support the development of tourism, as well as support with tourism plans and projects._x000D_ For this research the analytic - synthetic, ethnographic method was used, supported by the techniques of direct observation, signing, surveys, interview, each one with its respective instrument as field book, camera, survey questionnaire, interview guide and tokens Textual _x000D_ The theoretical support of the research is related to tourist conditions, natural resources, receiving community, road accessibility